The role of CXCR3 and its ligands in cancer - Wang, Xiaoming; Zhang, Yangyang; Wang, Sen; Ni, Hongyan; Zhao, Peng; Chen, Guangyu; Xu, Benling; Yuan, Long (Frontiers in Oncology, 2022)
Chemokines are a class of small cytokines or signaling proteins that are secreted by cells. Owing to their ability to induce directional chemotaxis of nearby responding cells, they are called chemotactic cytokines. Chemokines and chemokine receptors have now been shown to influence many cellular functions, including survival, adhesion, invasion, and proliferation, and regulate chemokine levels. Most malignant tumors express one or more chemokine receptors. The CXC subgroup of chemokine receptors, CXCR3, is mainly expressed on the surface of activated T cells, B cells, and natural killer cells, and plays an essential role in infection, autoimmune diseases, and tumor immunity by binding to specific receptors on target cell membranes to induce targeted migration and immune responses. It is vital to treat infections, autoimmune diseases, and tumors. CXCR3 and its ligands, CXCL9, CXCL10, and CXCL11, are closely associated with the development and progression of many tumors. With the elucidation of its mechanism of action, CXCR3 is expected to become a new indicator for evaluating the prognosis of patients with tumors and a new target for clinical tumor immunotherapy. This article reviews the significance and mechanism of action of the chemokine receptor CXCR3 and its specific ligands in tumor development.